PENGARUH BIAYA PROMOSI TERHADAP NET PROFIT MARGIN (NPM) PADA PERUSAHAAN SUB SEKTOR ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Nurlaelah Nurlaelah; Sahrul Falah (The Asia Pacific Journal Of Management Studies, 2017)
This study aims to determine the effect of Promotion Costs on Net Profit Margin in insurance sub-sector companies listed on the Indonesia stock exchange for the period 2009-2016. The type of data used in this study is secondary data in the form of financial statement data for each company that has been audited. The total population used in this study is 4 insurance companies, namely, Pt. ASBI, Pt. ASDM, Pt. ASRM, Pt. MREI. The sample selection was used in this researcher using a purposive sampling method so that the sample used was 32 corporate financial statement data. For independent variables, namely Promotion Costs, while for Net Profit Margin dependent. To test the hypothesis, it is used by using the t test of determination coefficient. The method used is analysis using simple linear regression analysis. While for data processing is done using the SPSS V. 20 program.The results of the study show that Promotion Costs significantly influence Net Profit Margin. What is intended by the value of t count <t table (-2,286> 2,042) significant value on the t test can be applied (0.029 <0.05). By showing the value of tcount> t table (-2,286> 2,042) and a significant value on the t test greater than the significant value set (0.029 <0.05). this means that partially promotion costs have a significant effect on Net Profit Margin. While the results of the test of determination coefficient show a value of 0.148 or 14.8% independent to explain the dependent variable is 0.148 or 14.8% while the remaining 85.2% is explained by other factors outside the research.